Systems Approach to targeted and long-acting HIV/AIDS therapy - Ho, Rodney J. Y. (Drug Deliv Transl Res, 2015)
Medication adherence and insufficient drug levels are central to HIV/AIDS disease progression. Recently, Fletcher et al. confirmed that HIV patients on oral antiretroviral therapy had lower intracellular drug concentrations in lymph nodes than in blood. For instance, in the same patient, multiple lymph node drug concentrations were as much as 99 % lower than in blood. This study built upon our previous finding that HIV patients taking oral indinavir had 3-fold lower mononuclear cell drug concentrations in lymph nodes than in blood. As a result, an association between insufficient lymph node drug concentrations in cells and persistent viral replication has now been validated. Lymph node cells, particularly CD4 T lymphocytes, host HIV infection and persistence; CD4 T cell depletion in blood correlates with AIDS progression. With established drug targets to overcome drug insufficiency in lymphoid cells and tissues, we have developed and employed a “Systems Approach” to engineer multi-drug-incorporated particles for HIV treatment. The goal is to improve lymphatic HIV drug exposure to eliminate HIV drug insufficiency and disease progression. We found that nano-particulate drugs that absorb, transit, and retain in the lymphatic system after subcutaneous dosing improve intracellular lymphatic drug exposure and overcome HIV lymphatic drug insufficiency. The composition, physical properties, and stability of the drug nanoparticles contribute to the prolonged and enhanced drug exposure in lymphoid cells and tissues. In addition to overcoming lymphatic drug insufficiency and potentially reversing HIV infection, targeted drug nanoparticle properties may extend drug concentrations and enable the development of long-acting HIV drug therapy for enhanced patient compliance.